Wide-band compact floating memristor emulator configuration with electronic/resistive adjustability. (November 2021) - Bhardwaj, Kapil; Srivastava, Mayank
Abstract: The article describes a floating voltage-controlled memristor emulator configuration based on single Dual Z output Voltage Dependent Transconductance Amplifier (DZ-VDTA). The DZ-VDTA is a dual Z output VDTA with provision of X port currents proportional to the differential Z ports' voltage. The presented memristor employs only two grounded passive elements without any use of bulky external analog multiplier, which is generally required to obtain the voltage dependent memductance expression of memristor. The prime advantages of proposed emulator can also be considered as the provision of electronic and resistance tuning available for controlling the emulated memristor behaviour and its wide operating frequency range from few KHzs to beyond hundred MHz. The designed circuit has been mathematically investigated for the consideration of parasitic elements of DZ-VDTA. Also, the operability of the developed floating memristor emulator has been checked through PSPICE generated simulations. Moreover, proposed memristor based relaxation oscillator has also been developed and verified. Finally, the implementation using LM13700 has been depicted.